2022
DOI: 10.3390/polym14030466
|View full text |Cite
|
Sign up to set email alerts
|

An In-Vitro Evaluation of Microleakage in Resin-Based Restorative Materials at Different Time Intervals

Abstract: A vital feature of conservative dentistry is the adhesion of the restorative material to the tooth structure for restoration of the tooth substance lost due to dental decay, trauma, or dental imperfections. In a perfect world, a restorative material should generate a lasting adhesion by bonding the restoration with tooth tissues. The ingress of micro-organisms, oral fluids, molecules, and ions through microscopic spaces due to faulty adhesion between restoration and tooth structure is known as microleakage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…The use of resin-based materials is gaining popularity in dental practice due to ease of application, excellent esthetic outcomes, adequate mechanical properties, and adaptability [7,18]. However, there are still a room for further modification of RBC due to some inherent drawbacks in these materials such as technique sensitivity, polymerization shrinkage which can lead to gap formation and microleakage, time needed for incremental application, low wear and abrasion resistance and marginal deterioration [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…The use of resin-based materials is gaining popularity in dental practice due to ease of application, excellent esthetic outcomes, adequate mechanical properties, and adaptability [7,18]. However, there are still a room for further modification of RBC due to some inherent drawbacks in these materials such as technique sensitivity, polymerization shrinkage which can lead to gap formation and microleakage, time needed for incremental application, low wear and abrasion resistance and marginal deterioration [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the success and failure of ceramic restoration by examining microleakage at the enamelceramic interface post-thermocycling utilizing the dye penetration method with 2% methylene blue dye [83]. Previous studies have suggested that methylene blue penetrates the deepest layer in WSLs (the inner half of enamel or outer half of dentin), secondarily through sound enamel (the outer half of the enamel), and penetrates the most shallow layer in infiltrant-treated WLSs (no penetration or the inner half of enamel) [84].…”
Section: Discussionmentioning
confidence: 99%
“…Este fue elegido porque no se han reportado fallas en este método para evaluar la microfiltración. Además, este colorante tiene mejor penetración en comparación con otros tintes, ya que, dentro de sus características, destaca su facilidad de manejo, su solubilidad en el agua y su rápida difusión en las grietas originadas por la microfiltración (24). Los resultados del presente estudio indicaron que la menor microfiltración reportada se dio en el grupo de la marca Ivoclar®, empleando la resina Tetric-N-Ceram® y su adhesivo universal Tetric N-Bond Universal® para restauraciones clase V. A pesar de que en el estudio in vitro realizado se controlaron variables con respecto a la técnica, se deberían realizar estudios que soporten el uso de resinas compuestas similares a las utilizadas en este estudio según la aplicación del fabricante, a fin de validar la sobrevida de estas resinas compuestas.…”
Section: Discussionunclassified